Managing Performance Signals Through Delay: Evidence from Venture Capital - Chakraborty, Indraneel; Ewens, Michael (Management Science, 2018)
This paper examines whether agency conflicts during venture capital (VC) fundraising impact investment behavior. Using novel investment-level decisions of VCs in the process of raising new funds, we find that venture capitalists take actions hidden from their investors—i.e., limited partners (LPs)—that delay revealing negative information about VC fund performance until after a new fund is raised. After fundraising is complete, write-offs double and reinvestments in relatively worse-off entrepreneurial firms increase. We find that these observations cannot be explained by strategic bundling of news or effort constraints due to the newly raised fund. Funds with both long and short fundraising track record exhibit this behavior and the delay is costly for fund investors (LPs). This strategic delay shows that fundraising incentives have real impacts on VC fund investment decisions, which are often difficult for LPs to observe. The Internet appendix is available at https://doi.org/10.1287/mnsc.2016.2662 . This paper was accepted by Gustavo Manso, finance.